2008
DOI: 10.1088/0034-4885/71/4/046901
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of cosmic magnetic fields

Abstract: We review the extensive and controversial literature concerning how the cosmic magnetic fields pervading nearly all galaxies and clusters of galaxies actually got started. Some observational evidence supports a hypothesis that the field is already moderately strong at the beginning of the life of a galaxy and its disc. One argument involves the chemical abundance of the light elements Be and B, while a second one is based on the detection of strong magnetic fields in very young high red shift galaxies.Since th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
379
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 405 publications
(397 citation statements)
references
References 119 publications
14
379
0
4
Order By: Relevance
“…Interestingly, similar magnetic fields have been observed in other spiral and barred galaxies [12][13][14] as well as galaxy clusters [15][16][17] and high redshift protogalactic structures [18]. It is generally believed that these magnetic fields are produced from the amplification of some seed fields [19] whose strength and origin are largely unknown [11,20]. The fact that the magnetic fields are present ubiquitously at high redshifts, strengthens the idea that their origin is cosmological, and magnetic fields may have pervaded the Universe in its hot early stages [18].…”
Section: Introductionsupporting
confidence: 59%
“…Interestingly, similar magnetic fields have been observed in other spiral and barred galaxies [12][13][14] as well as galaxy clusters [15][16][17] and high redshift protogalactic structures [18]. It is generally believed that these magnetic fields are produced from the amplification of some seed fields [19] whose strength and origin are largely unknown [11,20]. The fact that the magnetic fields are present ubiquitously at high redshifts, strengthens the idea that their origin is cosmological, and magnetic fields may have pervaded the Universe in its hot early stages [18].…”
Section: Introductionsupporting
confidence: 59%
“…Grasso & Rubinstein 2001;Kulsrud & Zweibel 2008;Ryu et al 2012;Widrow et al 2012). The first cosmological simulations had shown that primordial stars form in dark matter halos with 10 5 −10 6 M at z ∼ 20 (Abel et al 2002;Bromm et al 2002) or even earlier (Reed et al 2005;Gao et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, the origin of these fields remains largely uncertain (see Kronberg 1994;Grasso & Rubinstein 2001;Widrow 2002;Beck 2009, for reviews). A commonly accepted hypothesis is that relatively strong galactic and cluster magnetic fields result from the amplification of much weaker pre-existing "seed" fields via compression and turbulence/dynamo amplification in the course of structure formation processes (Kulsrud & Zweibel 2008).…”
Section: Introductionmentioning
confidence: 99%